PENGARUH CACAT LAS PADA SAMBUNGAN PIPA BAWAH LAUT (GIRTH WELD) DENGAN MENGAPLIKASIKAN FAILURE ANALYSIS DIAGRAM (FAD) - Suyadi, Suyadi (Vocational School Diponegoro University, 2010)
Suyadi, An under sea pipe connection (girth weld) is an area that possibly will get defect. This weld defects have a potential for causing tension concentration, so that there will be preliminary crack. This crack will spread due to cyclic loads received by the structure. This final assignment research is performed for evaluating mechanical integrity and girth weld having weld defect using method of Failure Analysis Diagram (FAD) and it takes a sample of case for South Sumatra West Java pipe belongs to PGN Co.Ltd. FAD is a method, which is good enough for evaluating the integrity of pipe structure having crack like flaw upon the weld. FAD divides two areas, namely safe area and unsafe area constructed by two axis, namely x axis that is stress ratio (Lr) and y axis that is stress intensity ratio (Kr). Stress ratio (Lr) is a ratio between a ref and a yield, mean while stress intensity ratio (Kr) is a ratio (stress intensity factor) between Kl and KIC (fracture toughness material). ANSYS 8.0 software is used for modeling by considering that the defect is in the form of semi elliptic with a/2c variation, that is 0,0469; 0,0938; 0,01406; and 0,1750. The loading upon the pipe is considered as the minimum loading (ï³pull = 8284.25 psi), medium (ï³pull = 41421.25 psi) and maximum (ï³pull = 82842.5 psi). From the analysis result, it is obtained that crack dimension with a/2c 0.175 is not safe upon minimum and medium loading, mean while upon the maximum loading condition, all modeled cracks dimensions cause the pipe is not safe. Keywords : pipeline, girth weld, semi elliptical defect, FAD.